Horticulture – A crowning glory in Agroforestry - Tewari, R. K.; Singh, Ramesh; Bajpai, C. K. (Indian Farming, 2015)
Agroforestry integrated with horticulture is quite remunerative, Top working of seed originated fruit plants like ber, aonla, karonda, mango etc. hold great promise. Homestead plantation of fruit plants can be encouraged with landless and marginal farmers. Due to woody nature, trees can withstand weather ragaries better than annual crops. Due to long life span and wide range diversity in flushing and fruiting it offers employment during off-crop season.